Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/his.12325
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile‐like (inflammatory/hyperplastic) mucosal polyps of the gastrointestinal tract in neurofibromatosis type 1

Abstract: NF-1-associated inflammatory polyps probably represent specific GI manifestations of this disorder, and should be considered, particularly in patients with GI symptoms. They should be distinguished from inflammatory fibroid polyps and from juvenile-like changes associated with ganglioneuroma/ganglioneuromatosis and neurofibroma/neurofibromatosis. Their aetiology remains obscure, but different mechanisms, including NF-1 inactivation, NF-1-associated vasculopathy, and localised mucosal prolapse/damage caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
34
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 29 publications
4
34
0
1
Order By: Relevance
“…Therefore, without knowledge of the clinical context pathologists should be careful about the exact type or aetiology of such polyps, as this may mislead clinicians in further patient management. In fact, some colonic polyps in the patient presented here were described as inflammatory polyps with granulation tissue and atypical stromal cells similar to some polyps in the report by Agaimy et al . (Figure ).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, without knowledge of the clinical context pathologists should be careful about the exact type or aetiology of such polyps, as this may mislead clinicians in further patient management. In fact, some colonic polyps in the patient presented here were described as inflammatory polyps with granulation tissue and atypical stromal cells similar to some polyps in the report by Agaimy et al . (Figure ).…”
supporting
confidence: 84%
“…Sir: With interest, but also concern, we read the article on juvenile‐like polyps in neurofibromatosis type 1 (NF‐1) by Agaimy et al . They present 15 patients (four new and 11 from the literature) with NF‐1 and one or more juvenile‐like/inflammatory/hyperplastic gastrointestinal polyps.…”
mentioning
confidence: 99%
“…leiomyosarcoma and osteosarcoma) and pheochromocytomas are associated with NF-1 [46 && , [47][48][49][50][51]. café au lait spots, axillary/inguinal freckling, and dermal neurofibromas) and ocular (i.e.…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…for their special interest in our recent publication in Histopathology , in which we described our experience with juvenile‐like inflammatory polyps presenting in different parts of the gastrointestinal (GI) tract in patients with certain ( n = 3) or probable ( n = 1) neurofibromatosis type 1 (NF1). We also reviewed the previous literature on similar cases, and found a total of 15 cases, including our patients . In their correspondence, the authors reported a unique case of concurrent NF1 (diagnosed at age 2 years and later confirmed genetically) and juvenile polyposis syndrome (JPS) (diagnosed at age 30 years) in the same patient.…”
mentioning
confidence: 95%